Interprofessional education for first year psychology students: career plans, perceived relevance and attitudes. Issue 3 (May 2015) - Roberts, Lynne D.; Forman, Dawn
Abstract Undergraduate psychology students have been largely excluded from interprofessional education (IPE) initiatives. In contrast to many health professions, undergraduate psychology students do not engage in work placements as part of their degree, and many enter careers outside the health care context. However, the collaborative skills gained through an IPE experience may well be beneficial to students who work in this wider context. This research examines whether undergraduate psychology students' views of IPE vary according to their planned career directions, and if so, whether the perceived relevance of IPE mediates the relationships. A sample of 188 Australian university undergraduate psychology students completed an online questionnaire following completion of a first-year IPE health sciences program. Path analysis indicated that psychology students' attitudes towards IPE are associated with both professional identification and practitioner orientation, fully mediated through the perceived relevance of IPE to future career and study plans. Stronger professional identification and practitioner orientation were associated with greater perceived relevance and more positive and less negative attitudes towards IPE. Placing a stronger emphasis on the generalizability of IP skills taught may increase students' awareness of the relevance outside of the health context, reducing disengagement of students planning alternative careers.